2005
DOI: 10.1021/es049149r
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Effect of Gold Mining and Damming on Mercury Contamination in Fish

Abstract: Since the late 1980s, several studies have shown that human populations in the Amazon basin are exposed to high mercury levels in their fish diet. Gold mining, which releases the metal during the amalgamation process and erodes soils naturally rich in mercury, is regarded as the main contamination source. Here, we present the results of a comparative study of mercury distribution in the water and fish of two adjacent rivers in French Guiana, with and without gold mining activities. As a consequence of a marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 31 publications
2
34
0
2
Order By: Relevance
“…Such unsafe concentrations of mercury present in the water, fish and sediments, pose serious threats to the giant otter, which depends on fish for its survival 4 Boudou et al, 2005;Durrieu et al, 2005).…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Such unsafe concentrations of mercury present in the water, fish and sediments, pose serious threats to the giant otter, which depends on fish for its survival 4 Boudou et al, 2005;Durrieu et al, 2005).…”
Section: A B C Dmentioning
confidence: 99%
“…Dias Fonseca et al (2005) analyzed different organs and tissues of two giant otters found dead in the Pantanal, in a region where no gold mining activity is reported, and found no evidence of contamination. However, especially in Brazil, where hydroelectric dams are an important component of development plans, a synergic effect of gold mining and damming on mercury contamination in fish should be considered as observed by Boudou et al (2005). They found that mercury mobilization related to gold mining account for even higher concentrations in fish when environmental conditions typical of a reservoir, such as anoxia, are present.…”
Section: A B C Dmentioning
confidence: 99%
“…Existem estudos que reportam, também, um incremento nas áreas à jusante de hidrelétricas, podendo atingir concentrações que representem um risco para a saúde das populações que dependem do consumo do peixe para sua subsistência (Verdon et al, 1991;Boudou et al, 2005;Hylander et al, 2006 (Veiga et al, 1994;Malm, 1998;Roulet et al, 1999;Wasserman et al, 2001;Lacerda e Malm, 2008).…”
Section: Introductionunclassified
“…In the Brazilian Amazon, for example, sediments from mining tailings in streams and rivers may vary between one and two tonnes per gram of gold produced [13]. One of the major impacts of water siltation is the increase in light attenuation by suspended particles, which can directly affect phytoplankton productivity by limiting the availability of Photosynthetic Active Radiation (PAR), and indirectly contribute to changes in biodiversity within rivers, including plankton [10], macroinvertebrates [14], and fish [15]. Specific to the Amazon Basin, a major reduction in phytoplankton density has been documented in Batata Lake due to a gain in suspended matter caused by mining activity [16].…”
Section: Introductionmentioning
confidence: 99%